Clinical Features of Severe or Fatal Mycoplasma pneumoniae Pneumonia - Izumikawa, Koichi (Frontiers in Microbiology, 2016)
Mycoplasma pneumoniae is one of the most common causes of community-acquired pneumonia in children and young adults. The incidence of fulminant M. pneumoniae pneumonia (MPP) is relatively rare despite the high prevalence of M. pneumoniae infection. This literature review highlights the clinical features of fulminant MPP by examining the most recent data in epidemiology, clinical presentation, pathogenesis, and treatment. Fulminant MPP accounts for 0.5–2% of all MPP cases and primarily affects young adults with no underlying disease. Key clinical findings include a cough, fever, and dyspnea along with diffuse abnormal findings in radiological examinations. Levels of inflammatory markers such as white blood cells and C-reactive protein are elevated, as well as levels of lactate dehydrogenase, IL-18, aspartate transaminase, and alanine transaminase. The exact pathogenesis of fulminant MPP remains unclear, but theories include a delayed hypersensitivity reaction to M. pneumoniae and the contribution of delayed antibiotic administration to disease progression. Treatment options involve pairing the appropriate anti-mycoplasma agent with a corticosteroid that will downregulate the hypersensitivity response, and mortality rates are quite low in this treatment group. Further research is necessary to determine the exact pathogenesis of severe and fulminant types of MPP.